Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Bank Syariah Mandiri di Banjarmasin Kalimantan Selatan - Restu Khaliq (Relevance: Journal of Management and Business, 2019)
The purpose of this study was to determine whether there was a significant effect of CARTER's service quality consisting of compliance, assurance, reliability, tangible, empathy, and responsiveness to customer satisfaction at Bank Syariah Mandiri Banjarmasin. Structural Equation Modeling (SEM) by smartPLS was used in the analysis data of this research. The sample of this study was 100 respondents, taken by random sampling technique. Data was collected using a questionnaire. The results showed that there was a significant effect of CARTER service quality consisting of compliance, assurance, reliability, tangible, empathy, and responsiveness to customer satisfaction at Bank Syariah Mandiri Banjarmasin because all T-Statistics values were above 1,960. The most dominant dimension in influencing customer satisfaction is a dimension of compliance regarding the application of Islamic sharia principles. Keywords: Service Quality, Customer Satisfaction, CARTER